Against ‘Migration’: Using Critical Realism as a Framework for Conducting Mixed-Method, Migrantization Research. - Iosifides, Theodoros (Journal of Critical Realism, 2017)
It is well acknowledged that the categorization of people with specific political, social and economic characteristics as ‘migrants’ – migrantization – is facilitated by mainstream, positivist versions of science and is associated with the production and/or reproduction of power relations. To date, this important critique has been advanced by academics influenced by interpretivism/poststructuralism who tend to relativize the discussion, and who are unable to provide a space for quantitative research. The main objective of this paper is to offer an alternative approach to avoiding positivism and relativism in ‘migration studies’, based on critical realism, which I term ‘migrantization research’. Critical realist migrantization research is multi-methodological and provides an interdisciplinary framework for conducting mixed-method social research on ‘migration’. It aims to discover, uncover or indicate how various causal powers – of structural, discursive/cultural and agential character – interact and produce certain outcomes. It presupposes that both measurable and non-measurable dimensions of the social world are relevant.